Determinan Struktur Modal Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Sub Sektor Makanan dan Minuman) - Diajeng Kusuma Wardani; Ronny Malavia Mardani; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine the direct effect of liquidity, profitability, company size on firm value. Knowing the direct effect of liquidity, profitability, company size on capital structure. Knowing the indirect effect of liquidity, profitability, company size on firm value through capital structure as an intervening variable on Manufacturing companies listed on the Indonesia Stock Exchange Food and Beverage sub-sector. The population of this study is 26 food and beverage companies that have been listed on the IDX. While the samples in this study were 19 companies.The results showed that liquidity had no significant effect on firm value. Profitability has a significant effect on firm value. While the size of the company has a significant effect on firm value. Liquidity has a significant influence on capital structure. Profitability has no significant effect on capital structure. The size of the company has no significant effect on capital structure. Capital structure has no significant effect on firm value. Determinant of capital structure on firm value in Manufacturing companies listed on the Indonesia Stock Exchange Food and Beverage sub-sector is liquidity while profitability and firm size are not determinants of capital structure in Manufacturing companies listed on the Indonesia Stock Exchange in Food and Beverage sub-sector in 2016-2018.Keywords: liquidity, profitability, company size, capital structure, company value.